2018
DOI: 10.1159/000489473
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Flex 19G Needles versus 22G Needles for Endobronchial Ultrasonography in Suspected Lung Cancer

Abstract: Background: A flexible 19-gauge (Flex 19G) needle has been developed for endobronchial ultrasonography. Objectives: We aimed to evaluate quantitative and qualitative specimen characteristics of Flex 19G in a randomized controlled setting for patients with suspected lung cancer. Methods: We undertook a single-center, randomized, controlled trial. A computer-generated randomization assigned all enrolled patients 1: 1 to undergo endobronchial ultrasonography using a Flex 19G or a 22-gauge (22G) needle for lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 17 publications
(19 reference statements)
1
28
0
Order By: Relevance
“…In other centers a part of these patients would include benign disease such post infection lymphadenopathy or sarcoidosis. We observed in our study again as it has been previously identified that 19G needle has larger biopsy sample almost double the size of a 22G needle 8 , 16 . The biopsy sample size was as follows in our study; d>c=b>a based on the needles.…”
Section: Discussionsupporting
confidence: 88%
“…In other centers a part of these patients would include benign disease such post infection lymphadenopathy or sarcoidosis. We observed in our study again as it has been previously identified that 19G needle has larger biopsy sample almost double the size of a 22G needle 8 , 16 . The biopsy sample size was as follows in our study; d>c=b>a based on the needles.…”
Section: Discussionsupporting
confidence: 88%
“…After validation by AccuRef Diagnostics, the sets of unstained slides (A‐D) were distributed to the 17 laboratories; some of the laboratories that specialized in NGS testing of cytological samples had also taken part in the working group of the latest annual meeting on molecular cytopathology held in Naples, Italy (Fig. ) . Each laboratory stained the slides by applying their own routine protocols (Diff Quik, Papanicolaou, or hematoxylin‐eosin staining).…”
Section: Methodsmentioning
confidence: 99%
“…For common indications, commercially available 21-or 22-gauge (G) needles were shown to be safe and equally effective in providing adequate diagnostic yield (5). More recently, a 19G needle has become commercially available and may provide the advantage of yielding larger cell blocks, possibly allowing to reduce the number of needle passes and overall procedure time, without compromising diagnostic accuracy (42)(43)(44). Biopsy specimens can also be obtained by transbronchial forceps introduced into the target lesion via the bronchial wall opening already established by the TBNA needle, thus providing histology-grade specimens and potentially increasing the diagnostic yield in certain benign and malignant conditions (45,46).…”
Section: Utility Of Convex-probe Ebus and Transbronchial Needle Aspiration In The Icumentioning
confidence: 99%